1997
DOI: 10.1002/(sici)1097-0215(19970117)70:2<241::aid-ijc16>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Circadian-system alterations during cancer processes: A review

Abstract: Murine and human data have indicated that tumors and tumor-bearing hosts may exhibit nearly normal or markedly altered circadian rhythms. Amplitude damping, phase shifts, and/or period (t) change, including appearance of ultradian rhythms (with t F 20 hr) usually become more prominent at late stages of cancer development. The extent of rhythm alterations also varies according to tumor type, growth rate and level of differentiation. While ''group chronotherapy,'' i.e., administration of the same chronomodulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
132
0
3

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(140 citation statements)
references
References 17 publications
5
132
0
3
Order By: Relevance
“…Indeed, in the presence of a tumour, daily activity levels of mice decreased over time which is in line with clinical reports of cancer patients (Mormont and Levi, 1997;Mormont et al, 2000). It is not clear what mechanism induces the reduction in activity in cachectic cancer patients.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Indeed, in the presence of a tumour, daily activity levels of mice decreased over time which is in line with clinical reports of cancer patients (Mormont and Levi, 1997;Mormont et al, 2000). It is not clear what mechanism induces the reduction in activity in cachectic cancer patients.…”
Section: Discussionsupporting
confidence: 82%
“…Chevalier et al (2003) reported that patients with advanced colorectal cancer showed less contrast between day time and night time activity (nocturnal sleep) . Individual activity patterns have even been suggested to be predictive of the patients' survival, tumour response and quality of life (Mormont and Levi, 1997;Mormont et al, 2000). The possibility of a tumour-induced disturbance in diurnal activity patterns is supported by our data, indicating a tumour-related shift in activity from the dark to the light period.…”
Section: Discussionmentioning
confidence: 99%
“…A disruption of the circadian cycle may result in disordered immune responses such as aberrant immune cell trafficking and abnormal cell proliferation cycles [30][31][32]. Sleep disorders, which result in an altered circadian rhythm, have been shown to affect the expression of the hypothalamic-pituitary-adrenal (HPA) axis.…”
Section: Possible Mechanisms: Clock-controlled Immune Functionmentioning
confidence: 99%
“…Indeed, up-to-severalfold changes in treatment tolerability and/or efficacy were found according to dosing time for 40 anticancer drugs in rodents (2). Moreover, the administration of anticancer agents at the circadian time when they were the safest also achieved best efficacy both in rodents (4) and in cancer patients (5)(6)(7)(8). Large intersubject differences in CTS further need to be taken into account for the personalization of circadian delivery of cancer treatments (9,10).…”
Section: Introductionmentioning
confidence: 99%